Implementasi Cooperative Learning Tipe Jigsaw Berbantuan Media Lapbook dalam Pembelajaran IPAS Sekolah Dasar - Devi Oktavini; D Wahyudin; Nurdian syah (Journal on Education, 2024)
This study aims to determine: (1) The improvement in students' learning outcomes in IPAS subjects through Jigsaw Cooperative Learning with lapbook media in the fourth grade at SDN Angkasa VI, (2) The enhancement of teacher activities using this method, and (3) The increase in student activities in IPAS learning in the fourth grade at SDN Angkasa VI. The research method used is classroom action research (CAR), consisting of three cycles of instructional improvement in the fourth-grade IPAS subject. The sample includes 41 fourth-grade students. The instruments used are student learning outcome tests, teacher and student observation sheets, and documentation. The conclusions are: (1) An improvement in students' learning outcomes from 7.31% in the pretest to 92.68% in the posttest of the third cycle, (2) An enhancement in teacher activities from 61.25% in the first cycle to 70% in the second cycle, reaching 78.75% in the third cycle, and (3) An increase in student activities from 48.75% in the first cycle to 70% in the second cycle, rising to 76.25% in the third cycle. Thus, the implementation of Jigsaw Cooperative Learning with lapbook media in IPAS learning for the fourth grade at SDN Angkasa VI has proven successful and shows improvement in each cycle.